School Well Being (SWB) and Learning Motivation of Psychology Students in the State University of Makassar - Dewi, Eva Meizara Puspita; Basti, Basti; Halima, Andi (Indonesian Journal of Educational Studies, 2021)
Students of the Faculty of Psychology in the State University of Makassar during online learning perceived the learning activities not effective due to internet cost, burdening course work, colliding lecture schedule, and inadequate learning facilities. To complete the program, students need supports on the school's well - being improvement. School well - being has an important role in supporting students' learning development and motivation in receiving materials from the teachers. The study aimed to describe students' learning motivation and school well - being in the Faculty of Psychology, The State University of Makassar. The research subjects were 201 students of the Faculty of Psychology, The State University of Makassar. The research instrument was the learning motivation and school well - being scale. Data were analyzed descriptively. Findings show that: 1) internal learning motivation was stronger than external learning motivation; 2) highest scores given to the campus facilities/ condition aspects were from students' batches 2019 and 2017, while many of students batch 2018 criticized the point. In terms of Social relationships, students batch 2019 experienced strong interaction with their friends and lecturers, while students batch 2017 perceived it weaker, and students batch 2018 thought that they had very rare interaction. 3) Students feel that the school's well - being was inadequate, but their learning motivation is still in the medium category, and even the internal motivation was higher than the external one